ANALISIS POTENSI KESULITAN KEUANGAN PERUSAHAAN MANUFAKTUR MAKANAN DAN MINUMAN DI BURSA EFEK JAKARTA - Nurraja, I Made Surya (Program Doktor Ilmu Ekonomi, 2008)
Many companies registred at the Bursa Efek Jakarta technically can’t be maintained anymore. This fact needs to be known earlier by who has concern for it. Therefore, the study produce a model for preventive action as an early warning system which expect can be used together in order to anticipate the financial condition of the companies are getting worse and finally become bankrupt.Using eleven financial rations and Multiple Discriminant Analysis, this study found that there are six financial rations have different between companies have significant contribution (Total Liabilities to Total Assets and Return on Equity)Keywords : Financial rations, Financial distress, Multiple Discriminant Analysis.